Structures and biological activities of azaphilones produced by Penicillium sp. KCB11A109 from a ginseng field. (February 2016) - Son, Sangkeun; Ko, Sung-Kyun; Kim, Jong Won; Lee, Jae Kyoung; Jang, Mina; Ryoo, In-Ja; Hwang, Gwi Ja; Kwon, Min Cheol; Shin, Kee-Sun; Futamura, Yushi; Hong, Young-Soo; Oh, Hyuncheol; et al.
Graphical abstract: Twelve azaphilones, including five previously unknown compounds, were isolated from the fungus Penicillium sp. derived from a ginseng field. Their structures were established by detailed spectroscopic analyses and chemical derivatizations. They were evaluated for cytotoxic, antimicrobial, antimalarial activities, and phenotypic effects in zebrafish development. Highlights: Twelve azaphilones, including five previously unknown compounds, were isolated from Penicillium sp. KCB11A109. Structures were determined by spectroscopic analyses and chemical derivatizations. Five azaphilones were found to induce phenotypic defects in zebrafish development. Abstract: Twelve metabolites, including five highly oxygenated azaphilones, geumsanols A–E, along with seven known analogues were isolated from Penicillium sp. KCB11A109, a fungus derived from a ginseng field. Their structures were assigned by spectroscopic means (NMR and MS), and stereochemistries were determined by extensive spectroscopic analyses ( 1 H– 1 H coupling constants, NOESY, and HETLOC) and chemical derivatizations (modified Mosher's method and acetonide formation). The isolates were evaluated for their anticancer, antimicrobial, antimalarial activities, and phenotypic effects in zebrafish development. Of these compounds possessing no pyranoquinone core, only geumsanol E exhibited cytotoxic activities and toxic effects on zebrafish embryos, suggesting that a double bond at C-11 and C-12 is important for biological activity.